Diversification Strategy for Sugar Palm Products in Rejang Lebong Regency, Bengkulu Province - Taufik Hidayat; Andi Ishak; Emlan Fauzi; Taupik Rahman; Ferdy Rosbarnawan; Harwindah Harwindah; Yueming Evendi; Nurdin Gultom; Rahmi Wati; Almidianto Hakim; Yahumri Yahumri; Alfayanti Alfayanti; Siti Rosmanah; Erpan Ramon; Jhon Firison (Institut Pertanian Bogor, 2025)
The sugar palm is one of the most important commodities in the Rejang Lebong Regency. Sugar palms have not been widely processed into value-added products because the community solely produces brown sugar. The goal of this study is to identify potential challenges and propose product diversification strategies that will boost the value added and sustainability of sugar palm firms in the Rejang Lebong Regency. This study was carried out in the Rejang Lebong Regency during August to October 2023. Data were gathered through observations, focus group discussions, and in-depth interviews. A fishbone diagram was used to identify potential and map product diversification challenges, while palm product diversification plans were developed using a strengths, weaknesses, opportunities, and threats (SWOT) matrix. The research results indicated that the diversification of sugar palm products is hindered by limited human resources in using technological innovations, restricted use of agricultural machinery, insufficient business partnerships, and local government programs that are not yet integrated into the development of product diversification. The strategy for sugar palm product diversification can be implemented by developing market alliances and improving processing technologies for MSMEs, with government program assistance and access to funding. This technique is expected to improve the quality and pricing of sugar palm products at the farmer level. Keywords: added value, aren palm, Arenga pinnata Merr, diversification strategy